Extravasation of radiopharmaceuticals: Why report? - Morgan, Thomas L. (Frontiers in Nuclear Medicine, 2023)
In this essay, I wish to discuss extravasation in the context of medical imaging and therapy with radiopharmaceuticals. Central to this discussion are two facts. First, they are easily identified, but the frequency of significant extravasations is unclear because there is no generally accepted definition of such an event. And second, there appears to be few reports of injuries from these events. The central thesis of this essay is that these events should be reported and followed so that agreement can be reached on the definition of a “significant” event which should be classified as a medical event in accordance with US Nuclear Regulatory Commission (NRC) regulations. I will also outline steps that can be taken to reduce the risk of extravasations.